The relationship between work environment and job performance among support staff in manufacturing industry at Intercity MPC Sdn. Bhd, Shah Alam / Noor Faizatul Ain Arshad - Arshad, Noor Faizatul Ain (2013)
The purpose of this paper is to examine the relationship between work environment and job performance among support staff in manufacturing industry at Intercity MPC Sdn Bhd, Shah Alam Selangor. The scope for this paper was included the whole of supporting staffs in this organization. For the methods, this paper is based on questionnaire data collected from 40 respondents in that organization. Included in the questionnaire are the demographic factors, work environment factors and also job performance factors. Correlation analysis is used to examine the relationship between variables. In findings, it was found that two variables that measure work environment are positively and significantly associated with job performance (leadership communication style and organization culture). Nevertheless, the demographic factors do not show a significant association with job performance (year of service and gender). Generally, the aim of this study is to see the relationship between work environment and job performance among support staff at Intercity MPC Sdn Bhd, Shah Alam, Selangor. For the recommendation, the researcher had suggested that the research about this kind of topic should add in Malaysia to make it as a reference for the other researcher. On top of that, the researcher also suggested that the organization should take an action included the physical setting, leadership communication style and organization culture to increased the job performance among their support staffs.